Hydatic cyst in communication with biliary tract.: Evacuation by a non dilated biliary tract. - Ferreira, Ciro; Alvarez, Carmelo; Geninazzi, Héctor; Bertolini, Carlos; Ruocco, Alvaro; Carbó, Alberto; Perdomo, Roberto (Cirugía del Uruguay, 1987)
Referred to an observation of hydatic cyst in communication with the peripheric biliary tract, the importance of been aware of the same is pointed out and of the evacuation of hydatic material to the biliary tract without canalicular dilatation. Also the importance of this fact should have in operatory procedures trying to avoid postoperatory compllcations is pointed out.